Violence Against Women and Children in Indonesia: A Threat to Human Security in the Era of Globalization - Zainuddin, Kusmawardany (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
In the long journey of life, women are loyal guides, always accompanying and guiding their children. However, who would have thought that violence against women and children is still a complex problem that continues to be in the global spotlight, especially in Indonesia. This problem is influenced by various types of factors, including patriarchal culture, economy, and also weak of law of enforcement. These acts of violence, weather physical, sexual or psychological, not only violate human rights but also hinder human development and create social instability. This phenomenon is not only a violation of human rights, but also a serious threat to human security that undermines the foundation of community welfare. The writing method used is literature study and secondary data analysis. This paper analyze how violence exacerbates the situation of globalization. In addition, this paper will also discuss how violence often experience psychological trauma, social difficulties, as well as a decrease in the quality of life. Therefore, comprehensive efforts involving the government and civil society are needed These efforts include strengthening law enforcement, increasing public awareness, and empowering women and children with a focus on prevention, protection, and recovery of victims